A REVIEW ARTICLE-GESTATIONAL DIABETES MELLITUS - C., Muhas; P., Naseef P. (International Journal of Current Pharmaceutical Research, 2016)
Diabetes mellitus is a chronic illness that requires continuing medical care and ongoing patient self-management education and support to prevent acute complications and to reduce the long-term complications. Moderate to severe maternal hyperglycemia in pregnancy has unique diabetes-related risks to mother and her unborn baby. So Gestational Diabetes mellitus (GDM) is a carbohydrate intolerance that is not diabetes that has developed or been discovered for the first time during pregnancy. Approximately 7% of pregnancies are affected by GDM. Patient with GDM are at higher risk for excessive weight gain, preeclampsia, and cesarean sections. Infants born to mothers with GDM are at higher risk for macrosomia, birth trauma, and shoulder dystocia. After delivery, these infants have a higher risk of developing hypoglycemia, hypocalcemia, hyperbilirubinemia, respiratory distress syndrome, polycythemia and subsequent obesity and type 2 diabetes. So the management of GDM is very important, and its management remains a challenge for the obstetricians and endocrinologists. MNT is the most common therapy which suffices for GDM, but when required. The pharmacological treatment becomes necessary, and the treatment of choice is human insulin. OHAs have also reached the high tables in the management of GDM. Glyburide and metformin have been found to be safe, effective and economical for the treatment of gestational diabetes. Let us join hands to manage the GDM effectively, not only for the present generation but also for the generations to come.